Pengembangan Kapasitas Kelembagaan dalam Mewujudkan Ketenagakerjaan Inklusif: Studi pada Unit Layanan Disabilitas Dinas Ketenagakerjaan Kota Medan - Emelia Emia Perbina Pinem; Muhammad Arifin Nasution (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The issue of limited employment access for persons with disabilities is a strategic concern that demands serious attention, particularly in Medan City. Unit Layanan Disabilitas (ULD) under the Department of Manpower of Medan City was established as a government initiative to support persons with disabilities in obtaining equal employment rights. ULD has demonstrated positive initiatives through skills training, coordination with companies, and the placement of workers with disabilities. However, its effectiveness in realizing inclusive employment still faces various internal challenges, such as limited personnel capacity and suboptimal work structure. The research method used in this study is qualitative with a case study approach. Data were collected through interviews, observations, and documentation studies. The data was analyzed qualitatively usingInstitutional Capacity Development indicators proposed by Merilee S. Grindle (1997), which include three dimensions: Human Resource Development, Organizational Strengthening, and Institutional Reform. The results of this study indicate thatthat in the dimension of human resource development, some ULD members have not received adequate training, there are no specialized assistants, and the recruitment process is not yet based on specific competencies. In terms of organizational strengthening, unclear division of tasks, weak internal communication systems, and suboptimal leadership in directing cross-sectoral teamwork were identified. Meanwhile, in the institutional reform dimension, there is still a lack of concrete policy support from the local government. Nevertheless, ULD has successfully facilitated the employment of 42 persons with disabilities in companies that provide inclusive job opportunities to fulfill the 1% employment quota for persons with disabilities